EKSPERIMENTASI MODEL BLENDED LEARNING TERHADAP HASIL BELAJAR MATA KULIAH APLIKASI KOMPUTER SPSS MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI - Muhammad Jainuri (Pendidikan Matematika | STKIP YM Bangko, 2019)
The purpose of this study is to describe the learning outcomes of SPSS Computer Application courses using blended learning models better than conventional learning. The study used a quantitative approach with the experimental method. The study population was all biology education study program students which numbered two classes with sample B as the experimental class and class A as the control class. The instruments used are the learning outcomes test questions in the form of descriptions. The results of data analysis requirements indicate that the data of the two sample classes are not normally distributed and have a homogeneous variance. Hypothesis testing uses two-independent formula samples with U-test (Mann Whitney). Based on the results of the analysis of research data shows that Sig. smaller than α or 0.007 <0.05 in the one-party test. Because Sig. <α then Ho is rejected and H1 is accepted, so it can be concluded that the learning outcomes of SPSS Computer Application courses using the blended learning model are better than conventional learning of biology education study program students. Keywords: blended learning model, conventional, learning outcomes